A single-output model for the dynamic design of constructed wetlands treating combined sewer overflow. (April 2018) - Pálfy, T.G.; Meyer, D.; Troesch, S.; Gourdon, R.; Olivier, L.; Molle, P.
Abstract: Constructed wetlands treating combined sewer overflow (CSO CWs) are vertical flow filters in France, with outflow limitation and detention basin. Treating storm-generated flows reduces pollutants and flow peaks entering natural waters. Storm-generated flows are stochastic and therefore optimized CSO CW design requires a dynamic approach, i.e., a modelling software targeting engineers. Therefore a new tool, called Orage, was developed. Orage consists of a core model, an iterative shell and a user interface. It optimizes dimensions and materials of CSO CWs site-specifically, based on inflow series and a low number of input parameters. The core model simulates hydraulics and TSS, COD and NH4 -N removal. Manual fitting of the core showed good results with a single load. The same parameters gave satisfying accuracy when simulating load series with closed material balance. Sensitivity analysis confirmed model robustness and justified coupling with an automatic shell algorithm for automatic optimization, based on a single output. Highlights: We developed a model for dual-sided CSO constructed wetlands. Calibration to an extreme load that our wetland failed to treat was accurate. The model showed stability with a series of loads. Simplified process descriptions led to good predictions. The model is robust and can serve automatic optimization for design-support.